2017
DOI: 10.1121/1.5014441
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics of the tense-lax stop contrast in Semarang Javanese

Abstract: Javanese has a contrast between tense and lax stops. While both tense and lax stops are voiceless and unaspirated, the contrast at least in word-initial position is realized through acoustic differences in the following vowel, including lower f0, breathier voice quality, and higher F1 for the lax stops relative to their tense counterparts. However, previous reports have indicated substantial cross-speaker variation, and in some cases involve differing characterizations of the acoustic contrast, possibly due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Both measures are predicted to be lower in breathier phonation than in modal phonation. HNR and/or CPP are useful for distinguishing phonation contrasts in many languages, including Chong (Blankenship, 2002), Jalapa Mazatec (Blankenship, 2002;Garellek & Keating, 2011), Ju|'hoansi (Miller, 2007), Southern Yi (Kuang, 2011), White Hmong (Esposito, 2012), Gujarati (Khan, 2012;Nara, 2017), Marathi (Berkson, 2019), Mon (Abramson, Tiede, & Luangthongkum, 2015), Chichimeco (Kelterer, 2017) and Semarang Javanese (Seyfarth, Vander Klok, & Garellek, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Both measures are predicted to be lower in breathier phonation than in modal phonation. HNR and/or CPP are useful for distinguishing phonation contrasts in many languages, including Chong (Blankenship, 2002), Jalapa Mazatec (Blankenship, 2002;Garellek & Keating, 2011), Ju|'hoansi (Miller, 2007), Southern Yi (Kuang, 2011), White Hmong (Esposito, 2012), Gujarati (Khan, 2012;Nara, 2017), Marathi (Berkson, 2019), Mon (Abramson, Tiede, & Luangthongkum, 2015), Chichimeco (Kelterer, 2017) and Semarang Javanese (Seyfarth, Vander Klok, & Garellek, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…However, a small percentage of /D/-series plosives were sometimes devoiced in this context, probably due to the presence of a preceding voiceless fricative in the carrier phrase. of the tense/lax or stiff/slack distinction in Javanese (Fagan, 1988;Seyfarth et al, 2017), but none of the speakers in our sample reported any fluency in this language.…”
Section: A Summary Of Resultsmentioning
confidence: 62%
“…5 Subsequently, articulatory maneuvers to sustain voicing for both the latter series could have conditioned the perceptually (Lotto et al, 1997) and typologically (Denning, 1989) expected changes in vowel height. Once the vowel height differences were phonologized, the redundant voicing for what is now the /TH/ series could be lost or variably realized (Brunelle et al, 2019;Seyfarth et al, 2017) (although recall that we did not find any evidence for variable realization in this data sample). The introduction of (something there was prestige associated with accurate pronunciation of borrowed items (cf.…”
Section: Diachronic Considerationsmentioning
confidence: 69%